Effect of hydrodynamic cavitation on zooplankton: a tool for disinfection - Sawant, Subhash Shivram; Anil, Arga Chandrashekar; Krishnamurthy, Venkat; Gaonkar, Chetan; Kolwalkar, Janhavi; Khandeparker, Lidita; Desai, Dattesh; Mahulkar, Amit Vinod; Ranade, Vivek Vinayak; Pandit, Aniruddha Balchandra (Biochemical Engineering Journal, 2008)
Application of hydrodynamic cavitation for disinfection of water is gaining momentum, as it provides environmentally and economically sound options. In this effort, the effect of cavitating conditions created by differential pump valve opening and that created by flowing through a cavitating element (orifice plates) on the microbes (zooplankton in sea water) is described. The experimental results are compared with modelling of cavitating conditions that includes cavity dynamics, turbulence generated by individual oscillating cavity, cell wall strength and geometrical and operating parameters of cavitation device. Theoretical model for quantifying the cavitationally generated turbulent shear and extent of microbial disinfection has been developed. Experimental results indicated that cavitation and/or turbulent fluid shear dominantly originating from cavitation are effective tools for sea water disinfection as more than 80% of the zooplankton present in the sea water were killed. It was also observed that shock waves generated due to cavitation is not the sole cause for zooplankton disruption. A correct physical mechanism accounting fluid turbulence and shear, generated from stable oscillation of cavity, significantly contribute towards the disruption. Further refinement of the model presented will serve as a basis for higher degree of disinfection and provide a practical tool for sea water disinfection. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Cell disruption; heat transfer; Hydrodynamic cavitation; Modelling; Wastewater treatment; Zooplankton